Strategi Pengembangan Perikanan Budidaya Air Laut di Kabupaten Kepulauan Mentawai - Agnes Sala Saluluplup; Alpon Satrianto (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to identify strategies for developing marine aquaculture, determine the position of marine aquaculture development, and formulate key strategic priorities for developing marine aquaculture in Mentawai Islands Regency. The methods used in this study are the SWOT and QSPM methods. The results of the study based on SWOT analysis indicate there are eight alternative strategies for the development of marine aquaculture, and the position of marine aquaculture development in Mentawai Islands Regency is in Quadrant IV (growing and developing) and VI (harvesting or divestment). Meanwhile, the primary priority strategies based on the QSPM analysis with the highest TAS values are: (1) enhancing human resource capacity through modern and sustainable aquaculture training, (2)establishing integrated marine aquaculture zones based on communities (marine farming villages) equipped with processing and marketing facilities, and (3) developing collaborative financing schemes (grants, CSR,village funds) for aquaculture infrastructure. The local government of Mentawai Islands Regency needs to formulate an integrated strategy for the development of marine aquaculture, including enhancing human resource capacity, adopting environmentally friendly technologies, developing supporting infrastructure, strengthening investment and market access, and fostering multi-stakeholder collaboration through financing schemes and cross-sectoral coordination.